Central Sensitization and Perceived Indoor Climate among Workers with Chronic Upper-Limb Pain: Cross-Sectional Study. (6th September 2015) - Sundstrup, Emil; Jakobsen, Markus D.; Brandt, Mikkel; Jay, Kenneth; Persson, Roger; Andersen, Lars L.
Abstract : Monitoring of indoor climate is an essential part of occupational health and safety. While questionnaires are commonly used for surveillance, not all workers may perceive an identical indoor climate similarly. The aim of this study was to evaluate perceived indoor climate among workers with chronic pain compared with pain-free colleagues and to determine the influence of central sensitization on this perception. Eighty-two male slaughterhouse workers, 49 with upper-limb chronic pain and 33 pain-free controls, replied to a questionnaire with 13 items of indoor climate complaints. Pressure pain threshold (PPT) was measured in muscles of the arm, shoulder, and lower leg. Cross-sectional associations were determined using general linear models controlled for age, smoking, and job position. The number of indoor climate complaints was twice as high among workers with chronic pain compared with pain-free controls (1.8 [95% CI: 1.3–2.3] versus 0.9 [0.4–1.5], resp.). PPT of the nonpainful leg muscle was negatively associated with the number of complaints. Workers with chronic pain reported more indoor climate complaints than pain-free controls despite similar actual indoor climate. Previous studies that did not account for musculoskeletal pain in questionnaire assessment of indoor climate may be biased. Central sensitization likely explains the present findings.